2022
DOI: 10.3389/fped.2022.830897
|View full text |Cite
|
Sign up to set email alerts
|

Ozone Exposure and Asthma Attack in Children

Abstract: BackgroundIncreasing evidence indicated that ozone (O3) exposure could trigger asthma attacks in children. However, the effect of O3 at low concentrations is uncertain.PurposeThis study aimed to explore the effects of O3 exposure at low concentrations on asthma attacks in children.MethodsA total of 3,475 children with asthma attacks from the First Affiliated Hospital of Xiamen University were available for the analyses. Air pollution data and meteorological data in Xiamen during 2016–2019 were also collected. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Acute ozone exposure in men causes sputum neutropenia in 30% of subjects, especially young children, women and those with persistent cardiorespiratory disease [ 32 ]. Exposure to O 3 can promote airway infections and increase the risk of asthma attacks [ 33 , 34 ]. A similar finding was noted in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Acute ozone exposure in men causes sputum neutropenia in 30% of subjects, especially young children, women and those with persistent cardiorespiratory disease [ 32 ]. Exposure to O 3 can promote airway infections and increase the risk of asthma attacks [ 33 , 34 ]. A similar finding was noted in our study.…”
Section: Discussionmentioning
confidence: 99%
“…A case-crossover study in China also reported that exposure to higher than 80 µg/m 3 O 3 increased the risk of reduced lung function. 34 Thus, patients with EOA could be the population at risk upon exposure to air pollution. We found that PM had distinct effects on endpoints in patients with asthma and allergic sensitization.…”
Section: Dovepressmentioning
confidence: 99%
“…PM 2.5 , NO 2 , SO 2 , and O 3 were significantly associated with increased risks of pediatric asthma ERVs in Shanghai, China [12]. An O 3 -8 h concentration above 80 µg/m 3 contributed to an increased risk of asthma attacks in children [13]. PM was related to motor vehicle emissions and industrial production was related to increasing pediatric asthma visits in USA [14].…”
Section: Introductionmentioning
confidence: 95%